Perfusion CT imaging of treatment response in oncology. Issue 12 (December 2015) - Prezzi, Davide; Khan, Aisha; Goh, Vicky
Highlights: Accurate assessment of treatment response is important for therapeutic triage. RECIST may underestimate response to anti-vascular agents. Changes in tumour vascularisation can be quantified by Perfusion CT. The short term effects of therapeutic agents on Perfusion CT parameters vary. Baseline intra-patient reproducibility studies are essential. Abstract: Perfusion CT was first described in the 1970s but has become accepted as a clinical technique in recent years. In oncological practice Perfusion CT allows the downstream effects of therapies on the tumour vasculature to be monitored. From the dynamic changes in tumour and vascular enhancement following intravenous iodinated contrast agent administration, qualitative and quantitative parameters may be derived that reflect tumour perfusion, blood volume, and microcirculatory changes with treatment. This review outlines the mechanisms of action of available therapies and state-of-the-art imaging practice.